Pemberdayaan Potensi Jemaat Dalam Membangun Gereja Misioner - Lexie Adrin Kembuan; I Wayan Sudarma (Sekolah Tinggi Teologi Anugrah Indonesia, 2021)
This paper discusses the potential empowerment of congregations for missioner churches. The Church is called a missioner when it is able to carry out programs that move outwards, not only perform services inward. The Church always motivates the congregation to preach the good news. The method used in this writing is a descriptive qualitative approach. The missioner church is always actively enhancing partnerships with churches or other mission institutions. In carrying out the activities out there is one concept of three and one that the author offers, namely in evangelism the author does activities by doing three things in one place. In the congregation, there are expected to be small groups engaged in a clear service program. In small groups, word sharing is done, evangelistic services, and at the same time the congregation runs its business.Keyword: Potential, congregation, missioner, empowerment, Church. AbstrakTulisan ini membahas tentang pemberdayaan potensi jemaat untuk gereja misioner. Gereja disebut misioner bila sudah mampu melaksanakan program yang bergerak ke luar, tidak hanya melakukan pelayanan ke dalam. Gereja selalu memberi motivasi kepada jemaat untuk memberitakan kabar baik. Metode yang digunakan dalam penulisan ini dengan pendekatan kualitatif deskriptif. Gereja yang misioner senantiasa aktif meningkatkan kemitraan dengan gereja-gereja atau lembaga-lembaga misi lainnya. Dalam melaksanakan kegiatan keluar dalam penginjilan gereja melakukan kegiatan dengan melakukan tiga hal dalam satu tempat. Dalam jemaat diharapkan ada kelompok-kelompok kecil yang bergerak mengerjakan program pelayanan yang jelas. Dalam kelompok kecil dilakukan sharing Firman, melakukan pelayanan penginjilan, dan sekaligus jemaat menjalankan usahanya.Kata-Kata Kunci: Potensi, jemaat, missioner, pemberdayaan, Gereja